Societal human resources management and development - Meirinhos, Viviana (2016)
Based on a broad conceptualization of Human Resources Management and Development (HRMD) as a technical, political, and strategic field concerned to managing and developing people within and towards work context(s), this research aims to explore a potential societal role of Human Resources (HR) profession. Framed on a larger project on “New Human Resources roles”, this particular study approaches HR profession by analysing its macro-societal challenges and intervention spaces.